Millennials in the Workplace: How Well-Being Affects Work Morale - Normillah, Niecen; Rahmah, Dian Dwi Nur (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Work engagement is a form of employee behavior in working conditions where an employee shows hope, intention, and commitment to the work he is doing, so that the employee carries out the work more actively. One of the factors that influence employee engagement is workplace welfare. This study aims to determine the relationship between working well-being and attachment in millennial generation employees. This research method uses a quantitative approach. The subjects of this study were 250 millennial generation employees who were selected using a purposive sampling technique. The data collection method used is the scale of work welfare and work engagement. The data analysis technique used is the Kendall Tau correlation test. The results showed that the P value < 0.05 and the results of the correlation value of 0.241 which has meaning in this study show that there is a positive and significant relationship between workplace welfare and work attachment in millennial generation employees. The practical implication in this study is that workplace welfare has an effective role in increasing employee work engagement, with the existence of a supportive work environment, facilities, and superiors that can provide encouragement in employees to contribute more to work to achieve company goals.Work engagement merupakan bentuk perilaku karyawan dalam bekerja keadaan dimana seorang karyawan menunjukkan harapan, niat, dan komitmen dengan perkerjaan yang digelutinya, sehingga karyawan tersebut menjalankan pekerjaan dengan upaya yang lebih. Salah satu faktor yang memengaru work engagement pada karyawan adalah workplace well-being. Penelitian ini bertujuan untuk mengetahui Hubungan workplace well-being dan keterikatan pada karyawan generasi milenial. Metode penelitian ini menggunakan pendekatan kuantitatif. Subjek penelitian ini berjumlah 250 karyawan generasi milenial yang dipilih dengan menggunakan teknik purposive sampling. Metode pengumpulan data yang digunakan adalah skala workplace well-being dan work engagement. Teknik analisa data yang digunkan adalah uji korelasi Kendall Tau. Hasil penelitian menunjukkan bahwa nilai P < 0.05 serta hasil nilai korelasi sebesar 0.241 yang memiliki arti dalam penelitian ini menunjukkan bahwa terdapat hubungan positif dan signifikan antara workplace well-being dengan work engagement pada karyawan generasi milenial. Implikasi praktis dalam penelitian ini adalah workplace well-being memiliki peran efektif dalam meningkatkan work engagement karyawan, dengan adanya lingkungan kerja, fasilitas, serta atasan yang mendukung dapat memberikan dorongan dalam diri karyawan untuk berkontribusi lebih dalam bekerja sehingga tercapainya tujuan perusahaan.